Effects of anti‐inflammatory drugs on the expression of tryptophan‐metabolism genes by human macrophages. Issue 4 (26th January 2018) - Regan, Tim; Gill, Andrew C.; Clohisey, Sara M.; Barnett, Mark W.; Pariante, Carmine M.; Harrison, Neil A.; ,; Hume, David A.; Bullmore, Edward T; Freeman, Tom C.
Abstract: Several lines of evidence link macrophage activation and inflammation with (monoaminergic) nervous systems in the etiology of depression. IFN treatment is associated with depressive symptoms, whereas anti‐TNFα therapies elicit positive mood. This study describes the actions of 2 monoaminergic antidepressants (escitalopram, nortriptyline) and 3 anti‐inflammatory drugs (indomethacin, prednisolone, and anti‐TNFα antibody) on the response of human monocyte‐derived macrophages (MDMs) from 6 individuals to LPS or IFN‐α. Expression profiling revealed robust changes in the MDM transcriptome (3294 genes at P < 0.001 ) following LPS challenge, whereas a more limited subset of genes (499) responded to IFNα. Contrary to published reports, administered at nontoxic doses, neither monoaminergic antidepressant significantly modulated the transcriptional response to either inflammatory challenge. Each anti‐inflammatory drug had a distinct impact on the expression of inflammatory cytokines and on the profile of inducible gene expression—notably on the regulation of enzymes involved in metabolism of tryptophan. Inter alia, the effect of anti‐TNFα antibody confirmed a predicted autocrine stimulatory loop in human macrophages. The transcriptional changes were predictive of tryptophan availability and kynurenine synthesis, as analyzed by targeted metabolomic studies on cellular supernatants. We suggest that inflammatory processes in the brain or periphery could impact on depression by altering the availability of tryptophan for serotonin synthesis and/or by increasing production of neurotoxic kynurenine.